Alteration in maxillary arch dimensions following preoperative nasoalveolar moulding therapy in bilateral cleft lip and palate patients - Dominika Magyar; Laura Pálvölgyi; Gwen Swennen; Sohaib Shujaat; Krisztián Nagy (Taylor & Francis Group, 2024)
Purpose Bilateral cleft lip and palate (BCLP) are severe congenital anomalies. The cleft interferes with the normal growth of the maxilla, leading to deficient midfacial development. The aim of the present study was to evaluate the short-term influence of preoperative nasoalveolar moulding (NAM) therapy on maxillary arch dimensions in patients with BLCP.Materials and methods 18 newborns (male: 12; female: 6) were recruited who underwent NAM therapy before cheiloplasty. The pre- (T0) and post-NAM (T1) plaster casts of the maxilla were scanned using a laboratory scanner. The measured parameters on the digital casts included premaxilla width, right and left alveolar cleft width, right and left molar region length, anterior interalveolar-, intercanine-, intermolar-, intertuberosity width, palatal length and anterior basal angle.Results Both left (p = 0.047) and right (p = 0.019) alveolar clefts significantly reduced in size at T1. A significant expansion in premaxilla width was detected (p = 0.037). Anterior basal angle showed a significant increase too. Except for the intermolar width (p = 0.045), no significant changes were identified in the transversal dimensions.Conclusion NAM therapy could potentially serve as an effective tool in mitigating the severity of bilateral cleft deformities at a short-term interval without interfering with maxillary growth. However, long-term studies are required to confirm the effectiveness of the therapy.